Validation of the German-language version of the Volition in Exercise Questionnaire (VEQ-D) - Pfeffer, I.; Elsborg, P.; Elbe, A. (German Journal of Exercise and Sport Research, 2020)
The present study describes the validation of the German Volition in Exercise Questionnaire (VEQ-D), an instrument to measure volition in the physical exercise context. Volition goes beyond the construct of motivation and describes self-regulatory mental processes that are responsible for initiating and maintaining a desirable action (e.g., exercising regularly). The six-factor scale structure of the original Danish version was confirmed in the translated questionnaire via a confirmatory factor analysis. The analyses showed a good model fit and satisfactory to good internal consistency. In addition, the VEQ-D showed criterion validity because it was able to predict physical exercise participation. It showed incremental validity by explaining additional variance with regard to self-efficacy and barriers for physical activity, which are well-established motivational predictors of physical exercise participation. Validation in other samples (e.g., in samples with lower physical exercise levels which are more representative of the general population) is, however, needed.